A tripartite multifactorial analysis of abstract anaphoric choice between this and this+NP in Chinese L2 English argumentative writing: Extending the usage-based approach to discourse alternation - Jianwei Xu; Ming Yue; Yujing Yang (PLoS ONE, 2026)
The usage-based approach has documented L2 learners’ general convergence with native speakers in the probabilistic constraint patterns governing syntactic alternations. However, whether this convergence pattern extends to discourse-level phenomena remains an open question. This study addresses this gap by examining the abstract anaphoric alternation between this and this +NP (reduced vs. explicit form) in argumentative writing. We analyze a dataset of 1,304 instances from L2 students (Mandarin Chinese-L1) and 1,303 instances from a native English baseline. Each instance was annotated for four discourse-internal factors— givenness , antecedent type , subjectness , and distance —operationalizing the economy-clarity trade-off of accessibility theory. A tripartite multifactorial analysis—examining constraint significance, ranking, and interactions—was conducted within each of three sequential phases: first, establishing an L1 baseline model; second, independently characterizing the L2 system; and third, conducting a direct statistical comparison. Results indicate that: (1) L1 choices are systematically constrained by multiple probabilistic competing factors; (2) when analyzed independently, L2 learners show sensitivity to the same core constraints, constraint hierarchy, and fundamental interaction logic as native speakers; and (3) statistical comparison confirms broad convergence, with the only reliable divergence localized to a single context: L2 learners overuse the explicit this +NP in the highest-accessibility topic-continuity context. These findings demonstrate that L2 learners exhibit largely the same fundamental constraint system that guides native speakers’ choices, extending the scope of usage-based explanations from syntactic alternations to discourse-level phenomena in second language research.